Duplicidad peneana en cuy (Cavia porcellus). Reporte de caso - Bautista-Solf, Merlit (2024)
The aim of this paper was to describe a case of penile duplication in a 2-month-old guinea pig in the Veterinary Pathology Laboratory of the Faculty of Veterinary Sciences of the National University of Cajamarca, Peru. The individual was 2 months old. The main anatomopathological findings are described. Complete duplication of the penis in an asymmetric frontal manner was evident.